Relationship between number of adult rumen fluke (Calicophoron microbothrioides) and eggs per gram of feces in culled dairy cattle in Peru: A pilot study. - Coronado León, J.F. (2024)
Background: Paramphistomosis, a parasitic condition caused by Calicophoron microbothrioides in domestic ruminants, has garnered limited attention among cattle breeders in the Cajamarca Valley, Peru. Despite its status as an endemic affliction with considerable risk, scant investigations have been conducted on this parasite within this region. Objective: This study aimed to assess the correlation between the population of adult parasites (referred to as “number of adult parasites” or NAP) in rumen and reticulum of naturally infected cows and the number of eggs per gram of feces (EPG). Methods: A sample of twenty-two cattle harboring adult parasites in their rumen and reticulum was selected for analysis. Fecal samples were collected from these animals to establish a correlation between NAP and EPG. Data analysis included linear regression, the Shapiro-Wilk normality test, and the nonparametric Mann-Whitney test. Results: The study revealed a remarkably strong and directly proportional association between the number of adult parasites in rumen and reticulum and the coproparazitologic EPG (r = 0.971). Conclusion: According to the linear model (NAP = 60.381 ± 3.37; EPG - 22.979) increasing EPG by one lead to an increase by 60 NAP in rumen and reticulum (p<0.01).